Collaborative Governance Penanganan Aksi Penyampaian Aspirasi Masyarakat di DPR RI - Farhan, Asna Alaili; Danu, Achmad; Asropi, Asropi; Rahayu, Neneng Sri (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research discusses collaborative governance in the handling of public rallies at the House of Representatives, focusing on the role of collaboration between the Police, Internal Security (Pamdal) of the House of Representatives, Members of the House of Representatives and Action Participants. This study uses Ansel and Gash's theory of collaborative governance which uses a participatory approach to manage rallies peacefully and productively. The study analyzed coordination mechanisms between stakeholders, public communication strategies, and challenges in maintaining openness and security. The results show that effective collaboration can increase the legitimacy of the aspiration process while minimizing the risk of conflict escalation and damage to public facilities.